2011
DOI: 10.1155/2011/624847
|View full text |Cite
|
Sign up to set email alerts
|

Incidental Findings on CT Scans in the Emergency Department

Abstract: Objectives. Incidental findings on computed tomography (CT) scans are common. We sought to examine rates of findings and disclosure among discharged patients who received a CT scan in the ED. Methods. Retrospective chart review (Aug-Oct 2009) of 600 patients age 18 and older discharged home from an urban Level 1 trauma center. CT reports were used to identify incidental findings and discharge paperwork was used to determine whether the patient was informed of these findings. Results. There were 682 CT scans … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
63
3
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(70 citation statements)
references
References 8 publications
(11 reference statements)
3
63
3
1
Order By: Relevance
“…Poor documentation has been described previously [9][10][11][12][13]. Its was shown that less than 20% of the patients with an incidental finding of moderate to severe concern had evidence of follow-up [11].…”
Section: Discussionmentioning
confidence: 97%
“…Poor documentation has been described previously [9][10][11][12][13]. Its was shown that less than 20% of the patients with an incidental finding of moderate to severe concern had evidence of follow-up [11].…”
Section: Discussionmentioning
confidence: 97%
“…1,2 Abdominal computed tomography (CT) has become the most common initial imaging test for suspected nephrolithiasis because of its high sensitivity for the diagnosis of urinary stone disease. 3 However, CT entails exposure to ionizing radiation with attendant longterm cancer risk, [4][5][6][7] is associated with a high rate of incidental findings 8,9 that can lead to inappropriate follow-up referral and treatment, 10 and contributes to growing annual care costs for acute nephrolithiasis, which are currently approximately $2 billion in the United States. 1,2 No evidence has shown that increased CT use, despite its higher sensitivity, is associated with improved patient outcomes.…”
mentioning
confidence: 99%
“…Thompson et al 24 described 31 incidental findings of sinus change in a total of 405 CT head examinations. This is equivalent to the rate of 7.6%.…”
Section: Discussionmentioning
confidence: 99%